Comparison of kinetics of the leg joints in seoi-nage between elite and college judo athletes - Ishii, T.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of the present study was to identify biomechanical factors that could be used for the evaluation of seoi-nage technique by comparing the techniques of elite and college-level judo athletes. The motion data of the seoi-nage were collected on three male elite judo athletes and nine male student judo athletes using a three-dimensional motion analysis technique and qualitatively compared. This study found that the peaks of the knee flexion torque, knee negative power, hip extension torque and hip positive/negative power on the swing leg of elite athletes was much greater than those of the college athletes. These indicated that the knee and hip joint contributed to the mechanical energy absorption of the tori`s body in the early phase and generated the positive power in the throwing phase.